PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE, KOMPETENSI AUDITOR, DAN TEKANAN WAKTU TERHADAP KUALITAS AUDIT - Fresia Elisabeth; Diana Frederica (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2026)
This study aims to analyze the effect of the use of Artificial Intelligence (AI), auditor competence, and time pressure on audit quality. The background of this study is based on the increasing complexity of the audit process and high demands for audit quality in the digital era. Although Artificial Intelligence is seen as a potential solution to improve audit efficiency, the role of auditors as human resources remains a major factor in determining audit quality. This study uses a quantitative approach with primary data obtained through questionnaires distributed to auditors at Public Accounting Firms (KAP) in the DKI Jakarta area. The number of respondents in this study was 106 auditors, and the data were analyzed using multiple linear regression with the help of IBM SPSS software version 25. The results of the study indicate that auditor competence has a positive and significant effect on audit quality, indicating that the knowledge, experience, and professional skills of auditors play a dominant role. Time pressure also has a significant positive effect on audit quality, indicating that well-managed time pressure can improve auditor efficiency and focus. Conversely, the use of Artificial Intelligence does not have a significant effect on audit quality, so that audit quality is determined more by internal auditor factors than by technology.Keywords: Use of Artificial Intelligence, Auditor Competence, Time Pressure, Audit Quality